Toxoplasma gondii Infection in Marine Animal Species, as a Potential Source of Food Contamination: A Systematic Review and Meta-Analysis - Ahmadpour, Ehsan; Rahimi, Mohamad Taghi; Ghojoghi, Altin; Rezaei, Fatemeh; Hatam-Nahavandi, Kareem; Oliveira, Sónia M. R.; de Lourdes Pereira, Maria; Majidiani, Hamidreza; Siyadatpanah, Abolghasem; Elhamirad, Samira; Cong, Wei; Pagheh, Abdol Sattar (Acta parasitologica, 2022)
Purpose Many marine animals are infected and susceptible to toxoplasmosis, which is considered as a potential transmission source of Toxoplasma gondii to other hosts, especially humans. The current systematic review and meta-analysis aimed to determine the prevalence of T. gondii infection among sea animal species worldwide and highlight the existing gaps. Methods Data collection was systematically done through searching databases, including PubMed, Science Direct, Google Scholar, Scopus, and Web of Science from 1997 to July 2020. Results Our search strategy resulted in the retrieval of 55 eligible studies reporting the prevalence of marine T. gondii infection. The highest prevalence belonged to mustelids (sea otter) with 54.8% (95% CI 34.21–74.57) and cetaceans (whale, dolphin, and porpoise) with 30.92% (95% CI 17.85–45.76). The microscopic agglutination test (MAT) with 41 records and indirect immunofluorescence assay (IFA) with 30 records were the most applied diagnostic techniques for T. gondii detection in marine species. Conclusions Our results indicated the geographic distribution and spectrum of infected marine species with T. gondii in different parts of the world. The spread of T. gondii among marine animals can affect the health of humans and other animals; in addition, it is possible that marine mammals act as sentinels of environmental contamination, especially the parasites by consuming water or prey species. Graphical Abstract